2013
DOI: 10.1177/2158244013503831
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Implementation of School-Wide Positive Behavior Intervention and Supports and Performance on State Accountability Measures

Abstract: This study examined data from 96 schools in a Southeastern U.S. state participating in training and/or coaching on School-Wide Positive Behavioral Interventions and Supports (SWPBIS) provided by the State Personnel Development Grant (SPDG) in their state. Schools studied either received training only (“non-intensive” sites) or training and on-site coaching (“intensive” sites). Fidelity of implementation was self-evaluated by both types of schools using the Benchmarks of Quality (BOQ). Some schools were also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Two of the most widely used and familiar versions of MTSS in schools are Response to Intervention (RtI) and Positive Behavioral Interventions and Supports (PBIS). Research shows that schools implementing MTSS had higher scores on academic accountability measures (Marin & Filce, 2013;McIntosh, Sadler, & Brown, 2012), significantly reduced office discipline referrals and suspension rates (Benner, Nelson, Sanders, & Ralston, 2012), and improved perceptions of school safety among school staff and students (Horner et al, 2009). MTSS implementation can also improve outcomes for students who may otherwise go underserved (Betters-Bubon, Brunner, & Kansteiner, 2016;McIntosh, Girvan, Horner, Smolkowski, & Sugai, 2014).…”
Section: Multi-tiered Systems Of Support and Comprehensive School Coumentioning
confidence: 99%
“…Two of the most widely used and familiar versions of MTSS in schools are Response to Intervention (RtI) and Positive Behavioral Interventions and Supports (PBIS). Research shows that schools implementing MTSS had higher scores on academic accountability measures (Marin & Filce, 2013;McIntosh, Sadler, & Brown, 2012), significantly reduced office discipline referrals and suspension rates (Benner, Nelson, Sanders, & Ralston, 2012), and improved perceptions of school safety among school staff and students (Horner et al, 2009). MTSS implementation can also improve outcomes for students who may otherwise go underserved (Betters-Bubon, Brunner, & Kansteiner, 2016;McIntosh, Girvan, Horner, Smolkowski, & Sugai, 2014).…”
Section: Multi-tiered Systems Of Support and Comprehensive School Coumentioning
confidence: 99%
“…However, some of these studies did not comprehensively consider implementation fidelity, which refers to the degree to which the core features of SWPBIS are implemented exactly as they are designed and intended. This is problematic considering the research that has found positive associations between implementation fidelity and positive academic and behavioral student outcomes (Marin & Filce, ; Pas & Bradshaw, ; Simonsen et al, ). Some of the studies that did not find a significantly positive relationship between SWPBIS and academic achievement either did not consistently measure implementation fidelity (e.g., Caldarella et al, ) or categorized or dichotomized implementation fidelity variables (e.g., Freeman et al, ; Gage, Sugai, Lewis, & Brzozowy, ; Noltemeyer et al, ), which limits the variability within these fidelity measures and also makes it more difficult to detect small changes in implementation.…”
Section: Outcomes Associated With Pbismentioning
confidence: 99%